PENGARUH PERSONAL COMPETENCE DALAM LITERASI MEDIA TERHADAP KEPERCAYAAN MAHASISWA PADA BERITA ONLINE - Adelia, Mentari; Desi Hasbiyah,; Agustini, (Karimah Tauhid, 2023)
Online news is a means of providing information for the people of Indonesia. The spread of hoax news is rampant, making people need to be careful in receiving information. Media literacy level is an important factor when it comes to analyzing online news content. This study aims to determine the effect of personal competence regarding clickbait online news on students' trust in news. Descriptive quantitative is the research methodology. Questionnaires and secondary data from online journals, publications, and books are used in primary data collection techniques. Research data analysis techniques using Likert scale measurements, WMS, and statistical tests of the effect of simple linear regression. The results of the research prove that personal competence regarding online clickbait news has a significant effect on students' trust in accurate online news. In conclusion, if the student's personal competence is good, the student's trust in accurate news will increase.